Tualang Honey formulation as potential osteoarthritis treatment: in-vitro genotoxicity outcome - Abd Rahim, Nour El Huda; Zulkifly, Ahmad Hafiz; Mohd Jan, Nurul Hafiza; Ibrahim, Mohd Zulfadzli; Mohamad Amri, Nur Fathonah; Hassan, Habibah; Rajab, Nor Fadilah (Malaysian Orthopaedic Association (MOA), 2024)
INTRODUCTION: Osteoarthritis (OA) is a degenerative joint disease affecting millions worldwide. In the orthopaedic field, viscosupplementation is used as an option treatment for pain relief among osteoarthritis patients. Tualang Honey Formulation (THF) (Patent no. MY179303-A) is currently being studied as a viscosupplement option for OA treatment. This study aimed to investigate the cell mutagenic effect after exposure to THF towards biocompatibility profile.